(untitled) (Bangladesh Journal of Microbiology, 2020)
A total of five Vibrio fluvialis organisms were isolated from the different environmental samples collected from Dhaka, Satkhira and Khulna. All these isolates were confirmed following API 20NE tests. Molecular analysis showed the absence of ctx, toxR, tdh, trh, stx1, and stx2 genes in these organisms. However, culture filtrates and crude proteins prepared from these organisms showed fluid accumulation in rabbit ileal loop assay, haemolysis of sheep red blood cess, rounding of BHK-21, HeLa and MDCK cells in cell culture assay, hind limb paralysis and death of mice in mice lethality assay and morphological changes in mouse neuronal cell assay. All these results indicated that the environmental V. fluvialis organisms, may not contain different virulence genes, including the ctx gene. However, the other in vivo and in vitro assays indicate that the toxins produced by the V. fluvialis organisms may contain enterotoxin, haemolysin, cytotoxin and neurotoxin. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 91-97